The reactions 203, 205 TI(x,t)204,206Pb - Nathan, O.; Bruge, G.; Brussière, A.; Kossanyi, P.; Loiseaux, J. M.; Roussel, P.; Testoni, J.; Valentin, L. (North Holland Publishin Co., 1968)
Fil: Nathan, O. Niels Bohr Institute; Dinamarca